Parity, bullying and confrontation in inclusive education - Olga Yu. Sinevich, Тatyana Yu. Chetverikova, Olga S. Kuzmina, (Opción, 2019)
The authors of the paper carried out a longitudinal study to characterize social and personal relations in inclusive practice among the participants of the educational process: teachers, children and parents. As a result, having to be involved in a continuous psychological struggle, each child is constantly under stress, which adversely affects their health and school performance. In conclusion, the destructive relationships between schoolchildren with and without disabilities are instigated by adults. Those are some parents of healthy children and teachers who lack theoretical, practical and personal readiness to work under inclusion.